Saccharomyces boulardii protects against murine experimental colitis by reshaping the gut microbiome and its metabolic profile - Gao, Hui; Li, Yinzheng; Xu, Jiqu; Zuo, Xuezhi; Yue, Tiantian; Xu, Huzi; Sun, Jie; Wang, Meng; Ye, Ting; Yu, Yan; Yao, Ying (Frontiers in Microbiology, 2023)
Saccharomyces boulardii (S. boulardii) has shown clinical beneficial effect in inflammatory bowel diseases recently. However, the underlying mechanisms remain incompletely understood. The aim of present study was to tested whether S. boulardii targets gut microbiota to protect against the development of experimental colitis in mice. Female C57BL/6 mice were gavaged with S. boulardii for three weeks before being challenged with dextran sulphate sodium to induce ulcerative colitis. Bodyweight, diarrhea severity, intestinal permeability, colonic histopathology, colonic inflammatory status, and epithelial cell death of mice were examined. The fecal microbiota and its metabolomic profiles were detected by 16S rDNA sequencing and UPLC-MS, respectively. Supplementation with S. boulardii significantly prevented weight loss and colon shortening, lowered colonic inflammation, ameliorated epithelial injury, and enhanced the intestinal barrier integrity in colitis mice. By inhibiting the abundance of pathogenic bacteria and increasing the probiotics abundance, S. boulardii improved the microbial diversity and restored the microbiota dysbiosis. Moreover, it also modulated microbial metabolome and altered the relative contents of metabolites involving amino acids, lipids, energy and vitamin metabolisms. These yeast-driven shifts in gut flora and metabolites are were associated with each other and with the inflammation profile in colitis. Collectively, S. boulardii exerts protective effects on colitis in mice by reshaping gut microbiome and its metabolic profile, indicating it as a promising therapeutic avenue.